RARE-23. DIFFUSE LEPTOMENINGEAL GLIONEURONAL TUMOR: A CASE SERIES. (1st June 2021) - Aaroe, Ashley; Ou, Alexander; McGovern, Susan; Paulino, Arnold; Johnson, Jason; Huse, Jason; Fuller, Gregory; de Groot, John; Walter, Andrew; Zaky, Wafik
Abstract: Introduction: Diffuse leptomeningeal glioneuronal tumor (DLGNT) is a rare diagnosis first incorporated into the WHO Classification of Tumors of the Central Nervous System in 2016. Though historically considered indolent, emerging evidence suggests that the biological behavior of these tumors may be further classified by molecular features of prognostic significance. Methods: A retrospective review was conducted in accordance with IRB approval of patients with the histologic diagnosis of DLGNT. Demographic, clinical, and molecular data where abstracted from the medical record when available. Results: 10 patients were identified (M = 8, F = 2). Median age at diagnosis was 6 years (range 0.3–21 years), and the most common symptoms at diagnosis were related to obstructive hydrocephalus, for which 3 patients required CSF diversion. MRI findings included diffuse leptomeningeal thickening, nodularity, or coating of the subarachnoid or ependymal surfaces. Histologically, these tumors expressed variable features of neuronal and/or glial differentiation. Four patients (40%) were treated with radiation therapy (all craniospinal), which was upfront for 2 patients. Chemotherapy regimens used included temozolomide, carboplatin and vincristine and vinblastine. NTRK or BRAF-targeted therapy were used upon progression. At follow-up, 6/10 had stable disease (4/6 of whom were on second line therapy), 1 had partial response, 1 passed away from sepsis and 2 were lost to follow-up. The median progression-free survival for the four patients who developed disease progression was 26 months (range 12–34 months). Next generation sequencing of the tumor tissue performed using a high-multiplex PCR-based NGS panel detected BRAF-KIAA1549 (4 patients) and NTRK (1 patient) fusions. Conclusions: DLGNT are rare tumors with scarce data about imaging characteristic and standard of care treatment. Our case series reinforces current literature that although these tumors appear low-grade, they can be clinically aggressive. Further study is needed regarding molecular diagnosis and profiling treatment strategies.